SNHG8 Promotes the Progression of Epstein–Barr Virus-Associated Gastric Cancer via Sponging miR-512-5p and Targeting TRIM28 - Zou, Changyan; Liao, Jinrong; Hu, Dan; Su, Ying; Lin, Huamei; Lin, Keyu; Luo, Xingguan; Zheng, Xiongwei; Zhang, Lurong; Huang, Tao; Lin, Xiandong (Frontiers in Oncology, 2021)
SNHG8 has been reported to act as an oncogene in gastric carcinoma (GC). However, its biological function in Epstein-Barr virus-associated gastric cancer (EBVaGC) remains unclear. This study investigated the role of SNHG8 in EBVaGC. 61 cases of EBVaGC , 20 cases of non-EBV-infected gastric cancer (EBVnGC) and relative cell lines were studied for the expression of SNHG8 and BHRF1 (BCL2 homolog reading frame 1) encoded by EBV with Western blot and qRT-PCR assays . The relation-ship between the expression levels of SNHG8 and the clinical outcome in 61 EBVaGC cases was analyzed. Effects of over-expression or knock-down of BHRF1, SNHG8 or TRIM28 on cell prolif-eration，migration, invasion and cell cycle and the related molecules were determined by several assays, including cell proliferation, colony assay，wound healing assay，transwell invasion assay, cell circle with flow cytometry, qRT-PCR and Western blot for expression levels, The interactions among SNHG8, miR-512-5p and TRIM28 were determined with Luciferase reporter assay, RNA immunoprecipitation (RIP), pull-down assays and Western blot assay. The in vivo activity of SNHG8 were assessed with SNHG8 knockdown tumor xenografts in Zebrafish. Results demonstrated that: (1) BHRF1 and SNHG8 was over-expressed in EBV-encoded RNA 1 positive EBVaGC tissues and cell lines. BHRF1 up-regulated the expressions of SNHG8 and TRIM28 in AGS; (2) SNHG8 over-expression had a significant correlation with tumor size and vascular tumor thrombus. Patients with high SNHG8 expression had poorer overall survival (OS) compared to those with low SNHG8 expression; (3) SNHG8 over-expression promoted EBVaGC cell proliferation, migration and invasion in vitro and in vivo, cell cycle arrested at the G2/M phase via the activation of BCL-2, CCND1，PCNA , PARP1, CDH1, CDH2 VIM and Snail; (4) Results of dual-luciferase reporter assay, RNA immunoprecipitation and pull-down as says indicated that SNHG8 sponged miR-512-5p, which targeted on TRIM28 and promoted cancer malignant behaviors of EBVaGC cells. Our data suggest that BHRF1 triggered expression of SNHG8, which sponged miR-512-5p and up-regulated TRIM28 and a set of effectors (such as BCL-2, CCND1,CDH1, CDH2 Snail and VIM) to promote EBVaGC tumorigenesis and invasion. SNHG8 could be an independent prognostic factor for EBVaGC and sever as target for EBVaGC therapy.